Synthesis and characterization of ordered mesoporous carbon: efforts to induce graphite and N-Fe doped materials - Hagman, Joel (My University, 2007)
In this thesis, eleven mesoporous carbon materials have been synthesized and characterized via an templatory method from an ordered mesoporous silica as template. This silica template were synthesized and characterized as well. The characterization of the carbon materials have been made with respect to structural order, substances incorporated, specific surface, specific pore volume, pore volume distribution and pore diameter. The methods used to perform the characterisations have been N2 physisorption, TEM, SEM-EDX, XPS, Raman, SAXS and WAXS. Some efforts have been made in order to dope the materials with N-Fe bonds as well as to induce graphitization. During the synthesisation the different materials differs in the carbon precursor, iron source and temperature treatment. The carbon precursors used have been furfuryl alcohol (FA), furfuryl amine (FAm), pyrrole (Py) and acrylonitrile (AcN). The iron source used have been FeCl3 dissolved in either paratoluene sulphone acid (PTSA), the carbon precursor or 1M HCl. The different temperature treatments have been made in such way that when the carbon precursor were to be pyrolysed, he material have been pyrolysed in either 800 °C or 1100 °C with N2 as inert atmosphere. All materials except those made from acrylonitrile have been impregnated three times with carbon precursor and then pyrolysed three times. The N2-physisorption of the acrylonitrile material showed that the pores of the silica template were totally filled with pyrolysed and polymerised carbon which made the material look finished and the silica removed after only on impregnation. unfortunately the pores must have collapsed or the carbon must have polymerised in the pore entrance since the amount of material after the removal of the silica were close to none. The other materials behaved normally and yielded approximately a 1:1 ratio between the amount of silica template used and the amount of carbon material achieved. The result of the experiments showed that the order of the mesoporous carbon depends on the type of carbon precursor as well as how the iron source were presented into the pores. FAm with the FeCl3 dissolved in the PTSA gave both a high Fe:N ratio and a clearly visible long range cubic ordered structure. The material were a bit more disordered if he FeCl3 were dissolved in the FAm and there were no long range order if FAm were used without any FeCl3. Using Py as carbon precursor gave the highest Fe:N ratio but the material were totally amorphous with respect to long range order. The acrylonitrile were hard to characterize since the amount of material were too little, but it appears to be difficult to dope the material with N and Fe and it seemed to lack long range order. The FA were used only as a reference and no FeCl3 were added to this material. However, the long range order were clearly cubic. Compared to the FAm, which have a similar monomer structure, the FA did not seem to need an iron source to gain long range order. All of the materials showed graphitic boundaries in both WAXS and Raman, but unfortunately there was impossible to measure the amount of these boundaries since the Raman results depended too much on where in the material the measurement were performed. Thus it is safest to say that the graphitization can be induced in pyrolysis at 800 °C but a higher temperature might give rise to more graphitization. The XPS results were used both together with the SEM-EDX to show the content of the materials as well as the Fe:N ratios but might would have given an information whether the nitrogen and iron present in the material were bound as C-N-Fe. Unfortunately the XPS spectras were not resolved enough to be able to tell all peaks apart and it we not possible to say if such bonds existed.
Keywords: Energi; Oorganisk kemi; Annan kemiteknik; Övrig teknisk materialvetenskap; Materialvetenskap; Energy; Inorganic Chemistry; Other Chemical Engineering; Other materials science; Materials Science